Solitude in older adults: a scoping review - Oliveira, Jaime Nuno Figueira Martinho (2023)
As individuals age, they may find themselves spending more time alone. Understanding the pathways and implications of this time spent in solitude on the global health and well-being of older adults is important for the clarification of this historically complex concept. This study aimed to map the existing research about solitude in older adults, focusing on its conceptualization, associated factors, and outcomes. A scoping review was performed with a search on Scopus, Web of Science, PubMed, and Academic Search Complete databases for publications until December 2022. Twenty-two studies were included. The main findings indicate that the conceptualization of solitude is ambiguous. While most studies (n = 14) adopted neutral definitions such as “being alone, voluntarily, without communicating with others”, a subset of studies deviated to alternative definitions incorporating a positive and/or negative dimension of the solitude state. These include alluding to “positive solitude” (as the choice of being with oneself, underscoring potential benefits), “inner-directed solitude”, “outerdirected solitude” and “negative affect and positive affect solitude”. Although this scoping review explicitly focused on the notion of solitude, conceptual variability was still observed on its association with social isolation and loneliness. The findings also shed light on the individual characteristics that may potentiate the benefits of solitude, such as higher levels of self-care, and a sense of control, and on the existence of both positive (e.g., opportunity for meaning) and negative (e.g., lower quality of life and well-being) outcomes. The spectrum of reported outcomes may reflect disparities in methodologies and conceptualizations of solitude, thus representing a need for further study and for an established and more consensual conceptualization.